Access to PrEP by cisgender mens and transsexual person: A qualitative study (Research, Society and Development, 2021)
A study carried out in Rio de Janeiro, investigates the perception of users of public services that offer HIV pre-exposure prophylaxis. Objective: To raise possible barriers and facilitating factors in accessing Pre-Exposure Prophylaxis (PrEP). Method: This is a research with a qualitative approach, conducted with users of services that offer PrEP in the greater Rio, interviews were recorded and transcribed. The analysis categories are derived from the construction of the experiences narrated by the interlocutors. Results and Discussion: 12 users of this therapy aged between 25 and 39 years were interviewed, 10 men who have sex with other men and 2 trans women. All users reported having some knowledge about PrEP; the transgender person is the one who attends the services least. There is a consensus that combined prevention is a positive step in the STI prevention policy. Conclusion: The main barriers are related to the structural limitations of health services.